High Throughput Receiver Structure for Underwater Communication - Chang-Uk Baek; Ji-Won Jung (International Journal of Distributed Sensor Networks)
Acoustic channels are characterized by long multipath spreads that cause intersymbol interference. The way in which this fact influences the design of the receiver structure is considered in this paper. To satisfy performance and throughput requirements, we propose a consecutive iterative BCJR equalization scheme. To achieve a low error performance, we resort to the powerful BCJR equalization algorithms to iteratively update probabilistic information between inner decoder and outer decoder. Also, to achieve a high throughput, we divide a long packet into a group of small consecutive packets, estimate channel information of the current packets, and use it to decode the next packets. Based on an experimental channel response, we confirm that the performance is indeed improved for long packet size.